Apostasy versus legitimacy: Relational dynamics and routes to resource acquisition in entrepreneurial ventures. (August 2014) - Stringfellow, Lindsay; Shaw, Eleanor; Maclean, Mairi
This article explores the relational dynamics of legitimation within a professional service venture context, using a Bourdieusian framework to elucidate the struggles for capital and legitimacy that characterise the venture development process. Two profiles of individual business owners who renounce or adhere to established norms of the professional field are identified: apostate and traditional . Small accounting ventures may benefit from improved access to resources if they concentrate on fitting in with prevailing small firm professional logics, eschewing logics from outside the focal field associated with apostates. A model of legitimacy is developed that accounts for the efficacy of institutional and strategic modes of legitimacy relative to the maturity of the field and objectification of its social formations. We propose that entrepreneurial habitus mediates field-level conditions and capital formations that, when combined, create symbolic capital and resource acquisition possibilities.